Pengaruh Sumber Nitrogen yang Berbeda dalam Medium Murashige dan Skoog (MS, 1962) terhadap Produksi Senesionin pada Kultur â€œCompact Globular Structureâ€ Crotalaria anagyroides H.B.K - Surakusumah, Wahyu (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
An Experiment on the effect of different nitrogen source in Murashige and Skoog media (MS, 1962) onÂ senesionin production of compact globular structure of Crotalaria anagyroides has been performed.Â CGS culture was obtained from callus culture on liquid MS media with 5.10-5 M NAA and 10-6 M kinetin. The CGSÂ was transfered into media with different nitrogen source: MS A (amonium+nitrat), MS B (nitrat) and MS C (amonium).Â Qualitatif data showed that senesionin could be detected in the CGS exstract by appearence of spot (Rf=0,78). The quantitative data showed that MS C was the best media to produce 4623 mg/DW senesioninÂ on 30th day.